Academic self-efficacy for high school scale: search for psychometrics evidence - Soely Polydoro (Estudos Interdisciplinares em Psicologia, 2015)
This article aims to present the adaptation and the search for psychometrics evidence of an academic self-efficacy scale. High school students (N = 453) participated of the research (mean age 15.93; SD 1.2). The Academic Self-efficacy Scale for High School is an adapted scale composed of 16 items and organized into three factors: self-efficacy for learning, self-efficacy to act in school life, and self-efficacy for the career decision. Through exploratory factor analysis, a KMO = 0.90 was verified, and 56.57% of the variance was explained. The internal consistency was 0.88. The scale demonstrated good conditions to identify academic self-efficacy of high school students.